Regulation of cocaine seeking behavior by locus coeruleus noradrenergic activity in the ventral tegmental area is time- and contingency-dependent - Solecki, Wojciech B.; Kielbinski, Michał; Wilczkowski, Michał; Zajda, Katarzyna; Karwowska, Karolina; Joanna, Bernacka; Rajfur, Zenon; Przewłocki, Ryszard (Frontiers in Neuroscience, 2022)
Substance use disorder is linked to impairments in the ventral tegmental area (VTA) dopamine (DA) reward system. Noradrenergic (NA) inputs from locus coeruleus (LC) into VTA have been shown to modulate VTA neuronal activity, and are implicated in psychostimulant effects. Phasic LC activity controls time- and context-sensitive processes: decision making, cognitive flexibility, motivation and attention. However, it is not yet known how such temporally-distinct LC activity contributes to cocaine seeking. In a previous study we demonstrated that pharmacological inhibition of NA signaling in VTA specifically attenuates cocaine-seeking. Here, we used virally-delivered opsins to target LC neurons for inhibition or excitation, delivered onto afferents in VTA of rats seeking cocaine under extinction conditions. Optogenetic stimulation or inhibition was delivered in distinct conditions: upon active lever press, contingently with discreet cues; or non-contingently, i.e. throughout the cocaine seeking session. Non-contingent inhibition of LC noradrenergic terminals in VTA attenuated cocaine seeking under extinction conditions. In contrast, contingent inhibition increased, while contingent stimulation reduced cocaine seeking. These findings were specific for cocaine, but not natural reward (food) seeking. Our results show that NA release in VTA drives behavior depending on timing and contingency between stimuli – context, discreet conditioned cues and reinforcer availability. We show that, depending on those factors, noradrenergic signaling in VTA has opposing roles, either driving CS-induced drug seeking, or contributing to behavioral flexibility and thus extinction.